Differential effects of elevated pCO2 and warming on marine phytoplankton stoichiometry. Issue 3 (21st January 2022) - Velthuis, Mandy; Keuskamp, Joost. A.; Bakker, Elisabeth S.; Boersma, Maarten; Sommer, Ulrich; van Donk, Ellen; Van de Waal, Dedmer B.
Abstract: Phytoplankton stand at the base of the marine food‐web, and play a major role in global carbon cycling. Rising CO2 levels and temperatures are expected to enhance growth and alter carbon:nutrient stoichiometry of marine phytoplankton, with possible consequences for the functioning of marine food‐webs and the oceanic carbon pump. To date, however, the consistency of phytoplankton stoichiometric responses remains unclear. We therefore performed a meta‐analysis on data from experimental studies on stoichiometric responses of marine phytoplankton to elevated p CO2 and 3–5° warming under nutrient replete and limited conditions. Our results demonstrate that elevated p CO2 increased overall phytoplankton C:N (by 4%) and C:P (by 9%) molar ratios under nutrient replete conditions, as well as phytoplankton growth rates (by 6%). Nutrient limitation amplified the CO2 effect on C:N and C:P ratios, with increases to 27% and 17%, respectively. In contrast to elevated p CO2, warming did not consistently alter phytoplankton elemental composition. This could be attributed to species‐ and study‐specific increases and decreases in stoichiometry in response to warming. While our observed moderate CO2 ‐driven changes in stoichiometry are not likely to drive marked changes in food web functioning, they are in the same order of magnitude as current and projected estimations of oceanic carbon export. Therefore, our results may indicate a stoichiometric compensation mechanism for reduced oceanic carbon export due to declining primary production in the near future.